2016
DOI: 10.1007/s00464-016-5134-0
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of robotic cholecystectomy versus laparoscopic cholecystectomy: operative outcomes and cost analysis

Abstract: Robotic cholecystectomy appears to be safe although costlier in comparison with laparoscopic cholecystectomy. Further studies are needed to understand the long-term implications of robotic technology, the cost to the health care system, and its role in minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 17 publications
1
26
0
2
Order By: Relevance
“…The primary difference was attributable to the amortized cost of the robot and consumables for the system. A more recent retrospective study demonstrates increase in total cost for MPRC ($8,870 MPRC vs. $5,771 LC) and a decrease in revenue (-$848 MPRC vs. $186 LC) (17). However there was a higher percentage of chronic cholecystitis in the MPRC cohort (27.9% MPRC vs. 14.4% LC), which may have contributed to the increased hospital costs.…”
Section: The Cost Of Robotic Surgerymentioning
confidence: 97%
“…The primary difference was attributable to the amortized cost of the robot and consumables for the system. A more recent retrospective study demonstrates increase in total cost for MPRC ($8,870 MPRC vs. $5,771 LC) and a decrease in revenue (-$848 MPRC vs. $186 LC) (17). However there was a higher percentage of chronic cholecystitis in the MPRC cohort (27.9% MPRC vs. 14.4% LC), which may have contributed to the increased hospital costs.…”
Section: The Cost Of Robotic Surgerymentioning
confidence: 97%
“…In a comparison study, Strosberg et al [8] demonstrated RC had significantly lower rates of intraoperative cholangiography and conversion to an open procedure, and concluded RC appeared to be a safe and feasible procedure although costlier in comparison with LC. In a nationwide database study by Salman et al [9] which described when overall cost was considered including length of stay, robotic surgery appeared to be cost-effective and as safe as nonrobotic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery and utilization of ICG may lead to a reduction in rates of conversion to open surgery [47,48]. In a large series of laparoscopic cholecystectomy, the rate of conversion is reported as 2.6-3%, with adhesions being the most common reason for conversion [49,50].…”
Section: Conversion To Openmentioning
confidence: 99%
“…Analyses of the outpatient costs of robotic-assisted cholecystectomy show higher total charges and costs when compared to laparoscopic surgery. However, proponents cite the numerous benefits of robotic surgery including enhanced surgeon ergonomics and the potential for building skills to perform more complex operations robotically [48,52]. In pediatric patients hospitalization cost for robotic compared to non-robotic averaged $11,000 vs. $7000 [26].…”
Section: Costmentioning
confidence: 99%